"EB, or Not EB?" Neonatal Desquamative Impetigo in a Degloving Pattern. Issue 2 (29th January 2016) - Nguyen, Tuyet A.; Wang, Audrey S.; Eichenfield, Lawrence F.; Barrio, Victoria
Abstract: We present the case of a 7‐day‐old boy with significant, rapidly spreading blistering and desquamation in a "degloving" pattern on the hands that mimicked epidermolysis bullosa but was ultimately diagnosed as bullous impetigo caused by a clinically aggressive strain of Staphylococcus aureus . Bullous impetigo is a desquamating condition caused by local release of S. aureus exfoliative toxin A and is more commonly seen in children. This case highlights the fragility of newborn skin and reviews the major diagnoses that should be considered in an infant with significant blistering.